Optimizing Exploration: Synergistic approaches to minimize false positives in pegmatite prospecting - A comprehensive guide for remote sensing and mineral exploration - Santos, D (2024)
Pegmatites represent a critical source of raw materials for the European Union's future, emphasizing the need to explore new deposits. Remote sensing plays a pivotal role in early-stage pegmatite exploration, generating prospectivity maps to facilitate field validation. The higher the false positive rate, the higher the time and costs required for field campaigns. This study aims to devise an approach that minimizes false positives, optimizing the work of the exploration field team. The proposed method seeks to create mineral prospectivity maps that accurately pinpoint high potential areas for pegmatite occurrences with minimal false positives occurrence through the application of fuzzy logic and leveraging the best mapping methods identified in prior research, in the Tysfjord region, northern Norway. Data from two multispectral satellites, namely WorldView-3 (WV3) and Sentinel-2, as well as light detection and ranging (LiDAR) data point cloud, were used, the last allowing the creation of a high-resolution hillshade map. Two classification methods were applied to the satellite images to leverage their individual advantages while minimizing possible weaknesses: the Mixture Tunned Matched Filtering (MTMF) using the Spectral Hourglass Wizard (SHW) Workflow and boosting through the LightGBM (LGBM) algorithm. These classification methods were employed to identify potential points for pegmatite exploration as these rocks have gained economic importance for being sources of raw materials such as high- purity quartz, ceramic feldspars, and Rare Earth Elements (REE). The high-resolution hillshade map was used to extract geological structures in the study area. The results of the fuzzy logic approach indicate potential locations of interest for pegmatite prospecting, providing a more comprehensive analysis of the remote sensing methods in the Tysfjord area. The resulting map seamlessly integrates into reports, streamlining field validation and supports informed decision-making. The methodology proposed in this study can be adaptable to other targets (minerals and rocks) and can be used as a guide for exploration worldwide.